The King's Horsemen in the Battle of Cunaxa. - Podrazik, Michał (Mnemosyne, 2023)
The scholarly debate on the Achaemenid Empire's cavalry pays only a little attention to the Great King's horsemen in the Battle of Cunaxa, fought in 401 BC between the forces of Artaxerxes II (404-359 BC) and his younger brother Cyrus. The same can be said of the discussion on the battle itself—Artaxerxes' horsemen are mentioned rather cursorily. The aim of the present article is to provide a closer look into Artaxerxes' cavalry in the Battle of Cunaxa, with particular attention paid to the horsemen commanded by Artagerses and by Tissaphernes.